PENGETAHUAN IBU YANG MEMILIKI ANAK BALITA TENTANG ISPA DIPUSKESMAS TENAYAN RAYA PEKANBARU - Delta Meda Aba; Arvina Sari Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Acute respiratory tract infections are infectious diseases of one or more respiratory tracts from the nose to the lung. So the purpose of the study is to know the knowledge of mother’s knowledge about acute respiratory tract infections in toddlers dipuskesmas tenayan raya. The type of this research is the quantitative design used is descriptive. The study was conducted in pekanbaru highway tenement in 2018. The population in this studi is the whole mother who has a toddler dipuskesmas tenayan raya pekanbaru. By way of sampling that is accidental and data analysis technique isunivariat. The result of research got the knowledge level of the parent about the dangers of acute respiratory infection in under fives majority. Majority not good 38 people 54% and minority good 32 person 46%. The conclusion of research result that has been done by researcher in may 2018 can be conluded that the knowledge picture of mother who have children under five about acute respiratory infection is less.